Neonatal intensive care unit nurses' perceptions and knowledge of newborn individualized developmental care and assessment program: A multicenter study - Rouya Baghlani; Mohammad-Bagher Hosseini; Abdolrasoul Safaiyan; Maedeh Alizadeh; Mohammad Arshadi-Bostanabad (Wolters Kluwer Medknow Publications, 2019)
Background: The newborn individualized developmental care and assessment program (NIDCAP) is a new multifaceted approach, which is developmentally and functionally supportive of health especially in premature newborns at the neonatal intensive care unit (NICU). This study is designed for assessing the knowledge and perception of nurses as the most important members of the multidisciplinary team of NIDCAP about this program. Materials and Methods: This cross-sectional study was conducted on 120 nurses working in the NICUs of Alzahra, Taleghani, and Children hospitals affiliated to the educational and treatment centers of Tabriz University of Medical Sciences as well as 29 Bahman Hospital affiliated to Tabriz Social Security Organization in 2016 using census sampling method. Three questionnaires were employed to collect demographic data and to explore the nurses' perceptions and knowledge of the NIDCAP program. Results: Findings of the study indicated that the mean (SD) nurses' knowledge and perception scores for NIDCAP were 71.83 (1.64) and 76.80 (0.79), respectively. In the terms of knowledge, significant differences were found with regard to being married (t = -2.39, p < 0.019), having an MSc degree (t = -2.14, p = 0.034), and employment experience (t = -3.38, p = 0.001). However, there was no significant relationship between perception and demographic variables (p > 0.05), nor was there any significant relationship between perception and knowledge (p = 0.275). Conclusions: The results of this study showed that the majority of nurses participating in the study had high knowledge about NIDCAP.